2014
DOI: 10.1089/pho.2013.3506
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biochemical Effects of 810 nm Diode Laser as an Adjunct to Periodontal Therapy: A Randomized Split-Mouth Clinical Trial

Abstract: Within the limitations of this study, the use of diode lasers as an adjunct to SRP produced significant improvements in clinical parameters as well as gingival crevicular fluid (GCF) IL-1β levels in the 6 month study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…In three studies, 31-33 the mean age of the patients was not reported. Eight studies 9,[15][16][17][18]27,28,30,33 reported the gender of participants. The study follow-up period ranged between 1 and 6 months ( Table 1).…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In three studies, 31-33 the mean age of the patients was not reported. Eight studies 9,[15][16][17][18]27,28,30,33 reported the gender of participants. The study follow-up period ranged between 1 and 6 months ( Table 1).…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
“…In 8 studies [16][17][18]28,33 , participants were nonsmokers. In studies by Zingale et al 15 and Kamma et al 9 the number of smokers were 2 and 18 patients, respectively.…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported SRP + L better than SRP alone. [10][11][12] In contrast to this, few studies found no additional effects of lasers. 37,38 Meta-analysis/systematic reviews also showed no additional effect of laser.…”
Section: Discussionmentioning
confidence: 86%
“…[7][8][9][10][11][12][13] Many studies have been reported the use of SRP + Laser but there are very few studies on lasers in maintenance phase. According to the best of author's knowledge, there are no reports evaluating the diode laser with the described parameters in our study during maintenance phase.…”
Section: Introductionmentioning
confidence: 99%